Evaluation of the Acute Hepatoprotective Potential of Hydroethanolic Extract of Duranta erecta L. Parts - Shadrack Donkor; Christopher Larbie; Gustav Komlaga; Benjamin Obukowho Emikpe (Journal of Toxicology, 2020)
Liver disease is a major health problem and its treatment is costly in most developing countries with attendant adverse effects. This study aimed at determining the acute hepatoprotective efficacy of Duranta erecta hydroethanolic extracts of leaves, ripe and unripe fruits against CCl4-, and acetaminophen-induced hepatotoxicity in animals. Materials and Methods. CCl4 (1 mL/kg body weight in olive oil) and acetaminophen (500 mg/kg b.wt) were used to induce hepatotoxicity in the animals. Animals were treated with extracts at 250 mg/kg b.wt and standard drug, silymarin (100 mg/kg), for 7 days. Hepatoprotective efficacy was assessed by assaying serum biochemical markers such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (γGT), bilirubin (Bil), antioxidative biomarkers including reduced glutathione (GSH), glutathione peroxidase (GPx), glutathione transferase (GST), superoxide dismutase (SOD), malondialdehyde (MDA), hydrogen peroxidase (H202), and nitric oxide (NO), as well as histological observations. Results. Exposure of the animals to CCl4 and acetaminophen resulted in liver injury as evidenced by elevated ALT, AST, ALP, γGT, Bil, MDA, H2O2, and NO levels with resultant derangement in liver microarchitecture. Pretreatment with hydroethanolic extracts, particularly ripe fruits of Duranta erecta, led to a reduction in these indicators and an increase in GSH, GPx, GST, and SOD levels. Biochemical data were supported by improvement in liver structure. Conclusion. The findings suggest that hydroethanolic Duranta erecta ripe fruits extract possesses hepatoprotective and antioxidative activities against CCl4- and acetaminophen-induced toxicity and could be developed as a potent agent for drug-induced liver diseases.